World Print Competition 77. : An international exhibition of prints, organized by the California College of Arts and Crafts in association with the San Francisco Museum of Modern Art. - Garlock, Trisha; Tsujimoto, Karen; California College of Arts and Crafts, San Francisco (San Francisco : San Francisco Museum of Modern Art, 1977)
Abu-Shakra, Walid ; Akins, Future ; De Almeida, David ; Alviani, Getulio ; Amano, Junji ; Andersch, Gisela ; Anderson, Robert ; Anderson, William T. ; Applegate, David C. ; Arakawa, Shusaku ; Arino, Pere ; Arsic, Miroslav C. ; Baker, Evelyn M. ; Balakjian, Marc ; Banerjee ; Barr, Caroline C. ; Barsch, Wulf E. ; Borcic, Bogdan ; Bravo, Michael ; Brown, Ian ; Buras, Maugo Maria ; Butler, Frances ; Butter, Thomas ; Capaci, Nick L. ; Cave, Jim ; Contaratou, Sosso ; Cortright, Steven ; Davies, Margaret C. ; De, Ranjit ; Demirli, Oya ; DioHandi ; Dolan, Don ; Duncan, Richard ; Dunikowski-Duniko, Wincenty ; Duttweiler, Bernard ; Evans, Roger T. ; Fong, Freddie ; Fontaine, Robert A. ; Fossum, Bruce ; Freed, David ; Frerichs, Karen E. ; Fridjonsson, Helgi Thorgils ; Funasaka, Yoshisuki ; Garza, Carmen Lomas ; Haage, Sixten ; Hagopian, Ruth ; Hatch, W.A.S. ; Hayler, Jeannette ; Herscher, Margaret ; Hersey, Dick E. ; Hettmansperger, Sue ; Heyman, Lawrence ; Hill, David W. ; Hirai, Kenzo ; Hiramatsu, Toshitsugu ; Horvat, Miljenko ; Hushlak, Gerald ; Igarachi, Agio ; Ito, Takashi ; Iwamasa, Ken ; Jacobson, Audrey ; James, John Gordon ; Janak, Alois ; Johnston, Ynez ; Jokanovic-Toumin, Dean ; Kagawa, Hidemi ; Kamatani, Shinichi ; Kanai, Masao ; Kaulitz, Hiroshi Kariya Garry ; Kiguchi, Keizo ; Knaan, Dan ; Kodaka, Hiroyuki ; Kohn, Misch ; Kokotovic, Ljubomir ; Kommers, Peter ; Kubo, Takuo ; Kucerova, Alena ; Kunimatsu, Asuka ; Langlois, Jean-Yves ; Leech, Merle ; Leuenberger, Werner ; Lima, Maria Tomaselli Cirne ; Loewensberg, Verena ; Lohse, Richard Paul ; Lucaci-Baias, Ethel ; Lyman, William III ; Mackechnie, John Allan ; Maki, Sheila ; Malina, Marian ; Martin, Dennis ; Masuda, Yoichi ; Matsutani, Takesada ; McBride, Robert ; McCormick, Thomas ; Merila, Vaino ; etc.
biografie
World Print Competition 77 : An international exhibition of prints, organized by the California College of Arts and Crafts in association with the San Francisco Museum of Modern Art, San Francisco, 1977
Engels
boek